A Critical Examination of Content Validity Evidence and Personality Testing for Employee Selection. (June 2021) - Fisher, David M.; Milane, Christopher R.; Sullivan, Sarah; Tett, Robert P.
Prominent standards/guidelines concerning test validation provide contradictory information about whether content-based evidence should be used as a means of validating personality test inferences for employee selection. This unresolved discrepancy is problematic considering the prevalence of personality testing, the importance of gathering sound validity evidence, and the deference given to these standards/guidelines in contemporary employee selection practice. As a consequence, test users and practitioners are likely to be reticent or uncertain about gathering content-based evidence for personality measures, which, in turn, may cause such evidence to be underutilized when personality testing is of interest. The current investigation critically examines whether (and how) content validity evidence should be used for measures of personality in relation to employee selection. The ensuing discussion, which is especially relevant in highly litigious contexts such as personnel selection in the public sector, sheds new light on test validation practices.